Pea, Bee, & Jay. 2, Wannabees - Smith, Brian (Comic book writer) (New York, NY : HarperAlley, an imprint of HarperCollinsPublishers, 2020)
"Who knew being queen could sting so much? All Bee really wants to do is play with her two best friends, Pea and Jay. But when she's replaced by Lenny--an ambitious bee hungry for power--as queen of her hive, the friends set out to prove Lenny isn't exactly who he seems to be"--Publisher marketing.
Keywords: Peas -- Comic books, strips, etc; Bees -- Comic books, strips, etc; Birds -- Comic books, strips, etc; Best friends -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Queens -- Comic books, strips, etc; Peas -- Fiction; Bees -- Fiction; Birds -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Kings, queens, rulers, etc. -- Fiction; Cartoons and comics; Comics (Graphic works); Graphic novels